Pemeriksaan Bakteri E.Coli pada Depot Air Minum Isi Ulang di Desa Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - M Fadly Kaliky; Siti Sangir Burham; Rahma Tunny (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Drinking water is a basic need for humans whose function is to maintain fluid balance in the body and help the metabolic process and every day humans need 1.5-2 liters of water to meet their needs (WHO 2019). To find out whether there are E.Coli bacteria in refill drinking water depots (DAMIU) in Tulehu Village, Salahutu District, Central Maluku Regency. This research is a descriptive survey. The data collection method is carried out by interviewing using questionnaires and taking samples before and after the processing process. based on the results of the study, 3 refill drinking water depots in Tulehu Village have met the requirements. The conclusion of this study is that 2 refill drinking water depots have met health requirements in accordance with the guidelines for inspecting drinking water depots based on the health regulations of the Republic of Indonesia no. 43 of 2014 concerning hygiene and sanitation of refill drinking water depots.